POLITICAL PARTIES IN UKRAINE AS A FORMAL RENT-SEEKING PATRON-CLIENT NETWORKS - Ганжа, А. М. (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science", 2017)
This article examines political parties  in Ukraine as  the  formal patron-client networks  that have as a major goal  the search of optimal position  for rent-seeking  in  the political market. The special attention is paid to a role of financial-industrial groups and clans in the forming and functioning of party`s institutes in the neopatrimonial political process